(3OaY EjQGOGJ NdjaI SdWGfs - (3GdLHYj GdYGedj GdCUHgGfj, SHW GdTgjO, Ydj Hf eMeO Hf MSf Hf Rjf GdOjf, J (B1103 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3Efj deG cfJ eTZhdG HcJGHI MGTjI TQM GddeYI hbY Edj MhGmT Ydi GdeLdO GdKGfj hChGNQ GdeLdO GdChd ef TQM GddeYI ddeQMhe GdeHQhQ NdjaI SdWGf Ydi GdcJGH GdePchQ (B...s
(3BNQgG (B:s
... (3hgfG eUdMI GdHGFY aeG fbd dHfGA GdHMK Ydjg ef GdYcS dG hLg dg hHbj eGOI dg Yf hGdOg heeG bQQfG jXgQ Cfg dG jMJGL Edi PcQg ef bhdg ShGA cGf eTJQjG (B...s
(3JHUQI GdYfhGf (B:s
(3GdQO Ydi GYJQGVGJ NdjaI SdWGf Ydi GdQhVI GdHgjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\14s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis